Identifying Opportunities for Virtual Reality Simulation in Surgical Education: A Review of the Proceedings from the Innovation, Design, and Emerging Alliances in Surgery (IDEAS) Conference: VR Surgery. (October 2015) - Olasky, Jaisa; Sankaranarayanan, Ganesh; Seymour, Neal E.; Magee, J. Harvey; Enquobahrie, Andinet; Lin, Ming C.; Aggarwal, Rajesh; Brunt, L. Michael; Schwaitzberg, Steven D.; Cao, Caroline G. L.; De, Suvranu; Jones, Daniel B.
Objectives . To conduct a review of the state of virtual reality (VR) simulation technology, to identify areas of surgical education that have the greatest potential to benefit from it, and to identify challenges to implementation. Background Data . Simulation is an increasingly important part of surgical training. VR is a developing platform for using simulation to teach technical skills, behavioral skills, and entire procedures to trainees and practicing surgeons worldwide. Questions exist regarding the science behind the technology and most effective usage of VR simulation. A symposium was held to address these issues. Methods . Engineers, educators, and surgeons held a conference in November 2013 both to review the background science behind simulation technology and to create guidelines for its use in teaching and credentialing trainees and surgeons in practice. Results . Several technologic challenges were identified that must be overcome in order for VR simulation to be useful in surgery. Specific areas of student, resident, and practicing surgeon training and testing that would likely benefit from VR were identified: technical skills, team training and decision-making skills, and patient safety, such as in use of electrosurgical equipment. Conclusions . VR simulation has the potential to become an essential piece of surgical education curriculum but depends heavily on the establishment of an agreed upon set of goals. Researchers and clinicians must collaborate to allocate funding toward projects that help achieve these goals. The recommendations outlined here should guide further study and implementation of VR simulation.